2017
DOI: 10.3390/w9020099
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Modeling to Assess Drought Resiliency of Snow‐Fed River Dependent Communities in the Western United States: A Case Study in the Truckee‐Carson River System

Abstract: Abstract:Assessing the drought resilience of snow-fed river dependent communities in the arid Western United States has taken on critical importance in response to changing climatic conditions. The process of assessing drought resiliency involves understanding the extent to which snow-fed dependent communities can absorb the effects of uncertain and variable water supplies while acknowledging and encouraging their capacity for adaptation. Participatory research approaches are particularly well suited to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The locally identified adaptation strategies in the Truckee-Carson River System case study reported here are informing the selection of adaptation measures to be simulated using a suite of hydrologic and operational models tailored to this river system [51,95]. To date, these adaptation measures focus on alternative water management strategies to enhance supply and include: reoperating federally managed Truckee River reservoirs to enhance surface water storage under earlier snowmelt regimes [96], constructing a reservoir in the Carson River headwaters to store snowmelt for downstream agricultural irrigation [97], and exploring managed aquifer recharge in the Carson Valley through off-season/winter irrigation in agricultural areas [98].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The locally identified adaptation strategies in the Truckee-Carson River System case study reported here are informing the selection of adaptation measures to be simulated using a suite of hydrologic and operational models tailored to this river system [51,95]. To date, these adaptation measures focus on alternative water management strategies to enhance supply and include: reoperating federally managed Truckee River reservoirs to enhance surface water storage under earlier snowmelt regimes [96], constructing a reservoir in the Carson River headwaters to store snowmelt for downstream agricultural irrigation [97], and exploring managed aquifer recharge in the Carson Valley through off-season/winter irrigation in agricultural areas [98].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, this qualitative interview study is part of a larger collaborative modeling research design implemented in the Truckee-Carson River System case study area [51]. Briefly, this project relies on iterative interaction with 12 water managers, each representing large numbers of individual water users that comprise the primary and diverse water uses geographically distributed from the headwaters to the system terminus [45,47,51,73].…”
Section: Collaborative Modeling Research Designmentioning
confidence: 99%
See 3 more Smart Citations